LPS nephropathy in mice is ameliorated by IL-2 independently of regulatory T cells activity. - Roberta Bertelli; Armando Di Donato; Michela Cioni; Fabio Grassi; Masami Ikehata; Alice Bonanni; Maria Pia Rastaldi; Gian Marco Ghiggeri (PLoS ONE, 2014)
Immunosuppressive regulatory T cells (Tregs) have been hypothesized to exert a protective role in animal models of spontaneous (Buffalo/Mna) and/or drug induced (Adriamycin) nephrotic syndrome. In this study, we thought to define whether Tregs can modify the outcome of LPS nephropathy utilizing IL-2 as inducer of tissue and circulating Tregs. LPS (12 mg/Kg) was given as single shot in C57BL/6, p2rx7⁻/⁻ and Foxp3EGFP; free IL-2 (18.000 U) or, in alternative, IL-2 coupled with JES6-1 mAb (IL-2/anti-IL-2) were injected before LPS. Peripheral and tissue Tregs/total CD4+ cell ratio, urinary parameters and renal histology were evaluated for 15 days. IL-2 administration to wild type mice had no effect on peripheral Tregs number, whereas a significant increase was induced by the IL-2/anti-IL-2 immunocomplex after 5 days. Spleen and lymph nodes Tregs were comparably increased. In p2rx7⁻/⁻ mice, IL-2/anti-IL-2 treatment resulted in increase of peripheral Tregs but did not modify the spleen and lymph nodes quota. LPS induced comparable and transient proteinuria in both wild type and p2rx7⁻/⁻ mice. Proteinuria was inhibited by co-infusion of human IL-2, with reduction at each phase of the disease (24 -48 and 72 hours) whereas IL-2/anti-IL-2 produced weaker effects. In all mice (wild type and p2rx7⁻/⁻) and irrespective of treatment (IL-2, IL-2/anti-IL-2), LPS was associated with progressive signs of renal pathologic involvement resulting in glomerulosclerosis. In conclusion, IL-2 plays a transient protective effect on proteinuria induced by LPS independent of circulating or tissue Tregs but does not modify the outcome of renal degenerative renal lesions.